PENGEMBANGAN MOTORIK KASAR ANAK USIA DINI MELALUI PERMAINAN KREATIF - Asyruni Multahada; Pingky Melaty; Heni Apriyani; Tris Andriani (Fakultas Tarbiyah Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
One of the abilities of children who are developing at an early age is motor skills. Aspects of motor development is one aspect of development that can integrate the development of other aspects. Motor development in children has a very important role. The child's inability to perform physical movements will foster a sense of insecurity. One aspect of motor development that needs to be considered is the aspect of gross motor development in children. The problem of obesity is high enough to appear in early childhood. This happens due to the lack of physical activity carried out by children. Therefore, we need some activities that stimulate movement activity in children. Fun movement activities can be done through creative games because the world of children is the world of play. Playing creative games is a very important activity to stimulate children's gross motor growth and development, because playing is a source of learning for children. Therefore, teachers need to apply creative games that vary every day.